RNase J1 and J2 Are Host-Encoded Factors for Plasmid Replication - Guimarães, Vanessa Andrade; Le Scornet, Alexandre; Khemici, Vanessa; Hausmann, Stéphane; Armitano, Joshua; Prados, Julien; Jousselin, Ambre; Manzano, Caroline; Linder, Patrick; Redder, Peter (Frontiers in Microbiology, 2021)
Plasmids need to ensure their transmission to both daughter-cells when their host divides, but should at the same time avoid overtaxing their hosts by directing excessive host-resources toward production of plasmid factors. Naturally occurring plasmids have therefore evolved regulatory mechanisms to restrict their copy-number in response to the volume of the cytoplasm. In many plasmid families, copy-number control is mediated by a small plasmid-specified RNA, which is continuously produced and rapidly degraded, to ensure that its concentration is proportional to the current plasmid copy-number. We show here that pSA564 from the RepA_N-family is regulated by a small antisense RNA (RNA1), which, when over-expressed in trans, blocks plasmid replication and cures the bacterial host. The 5′ untranslated region (5′UTR) of the plasmid replication initiation gene (repA) potentially forms two mutually exclusive secondary structures, ON and OFF, where the latter both sequesters the repA ribosome binding site and acts as a rho-independent transcriptional terminator. Duplex formation between RNA1 and the 5′UTR shifts the equilibrium to favor the putative OFF-structure, enabling a single small RNA to down-regulate repA expression at both transcriptional and translational levels. We further examine which sequence elements on the antisense RNA and on its 5′UTR target are needed for this regulation. Finally, we identify the host-encoded exoribonucleases RNase J1 and J2 as the enzymes responsible for rapidly degrading the replication-inhibiting section of RNA1. This region accumulates and blocks RepA expression in the absence of either RNase J1 or J2, which are therefore essential host factors for pSA564 replication in Staphylococcus aureus.